Antioxidant and Anti-Inflammatory Efficacy of Dipsacoside B in Ameliorating Myocardial Infarction in an in vivo Model - Han, Xiao; Chen, Fang; Zhao, Jinying (Indian Journal of Pharmaceutical Education and Research, 2018)
Background: Myocardial Infarction (MI) is a severe coronary ailment associated with a great risk of mortality, often contributing to sudden cardiac death. Cardiovascular diseases account for approximately 32% of global deaths, with MI representing 85% of these cases, necessitating immediate and extensive medical intervention. Objectives: In this study, we investigated the therapeutic efficacy of the triterpenoid saponin dipsacoside B in alleviating myocardial infarction. Materials and Methods: Myocardial Infarction (MI) was induced in healthy male rats using Isoproterenol (ISO). Following this, the rats received treatment with two distinct concentrations of dipsacoside B. The study utilized both pre-treatment and co-treatment protocols with dipsacoside B in the ISO-induced MI rats. The cardioprotective and anticholesteremic effects of dipsacoside B were evaluated through hemodynamic assessments and serum lipid profile analysis. To determine the compound's oxidative stress scavenging potential, antioxidant levels were quantified in the experimental animals. Furthermore, the therapeutic effectiveness of dipsacoside B was evaluated by analyzing important myocardial biomarkers such as TGF-β, cTnI, BNP, MYO, H-FABP, GP-BBP, and CK-MB. Results: The anti-inflammatory and anti-apoptotic properties were investigated by measuring levels of inflammatory proteins and caspases in the MI-induced rats receiving dipsacoside B treatment. To confirm the antioxidant defense potential of dipsacoside B, Nrf2 protein levels were analyzed. The results demonstrated that dipsacoside B effectively regulated serum lipid profiles and improved hemodynamic parameters in MI-induced rats. Treatment with dipsacoside B significantly reduced critical MI mediators, restored antioxidant levels, and mitigated oxidative stress. Furthermore, dipsacoside B suppressed inflammation and apoptosis, as evidenced by reduced inflammatory markers and caspase activity. Importantly, Nrf2 protein expression was markedly upregulated, confirming the antioxidant defense capacity of dipsacoside B. Conclusion: In conclusion, our findings indicate that dipsacoside B exhibits strong antioxidant, anti-inflammatory, and cardioprotective properties, making it a promising therapeutic agent for alleviating myocardial infarction.
Keywords: Myocardial infarction; ISO MI in vivo model; Phytochemical; Dipsacoside; Antioxidant; Anti-inflammatory agent